Accidental Impacts on Historical and Architectural Heritage in Port Areas: The Case of Brindisi. Issue 2 (17th February 2017) - Martino, Antonello; Fatiguso, Fabio; De Tommasi, Giambattista; Casal, Joaquim
ABSTRACT: Most port areas can produce impacts on the historical and architectural heritage, leading to rapid pathological effects and generating high risks in terms of damages and losses of historical, artistic, and cultural values. In effect, in addition to stationary actions (air pollution, waste, water discharge), port activities could generate exceptional impacts: the so-called "major accidents", such as fires or explosions and chemical releases. The present contribution analyses and discusses a given case, the port of Brindisi, suggesting a methodology for the assessment of exceptional impacts in ports, in order to identify those potential accidents and their effects on the historical landscape. It points out that, as often occurs in ports, the most frequent major accidents are caused by activities involving hazardous materials. The methodology proposed for this given case aims to demonstrate that in the historical port areas, such as in the Mediterranean Sea, the development and management should be accompanied, or even oriented to the protection of the historical and cultural landscape.